La science-fiction au prisme de l’intime : étude des séries Lupus et Aâma de Frederik Peeters (2002-2014) - Alain Boillat (ReS Futurae, 2019)
The article focuses on Lupus and Aâma, two series of four comic books written and drawn by the Genevese author Frederik Peeters, which are considered in their respective internal logic, in a comparative way and in their relationship with certain stereotypes of the science-fiction bande dessinée. The generic expectations created by the comic books of Peeters are discussed in particular on the basis of the cover images and the first panels of the albums. The emphasis is on the gap established by Peeters with certain conventions of the genre, since introspection and everyday life are in both series privileged on exoticism and spectacular: introspection is superimposed on spatial exploration. In particular, we show how, from one series to another as well as from one volume to another in the second series, the author gradually appropriates certain generic characteristics that he nevertheless formulates in a personal way. The study of graphic and narrative recurrences leads us to hypothesize that the stories can be read as an expression of an ambition to propose an adult science-fiction comic book as a continuation of Mœbius and autobiographical comics, and which therefore reflects the subjective orientation taken by some novelists in the field of science-fiction literature since the 1970s.